Renowned academician Awang Had dies at 79: Eminent figure: He was multi-talented and headed universities - Perimbanayagam, Kalbana; Idris, A.Azim (New Straits Times, 2013)
RENOWNED academician Professor Tan Sri Dr Awang Had Salleh leaves behind a remarkable legacy in the country's education system. The 79-year-old Penang born, who had been ill for almost a decade, died yesterday at 3.03am at the Putrajaya Hospital due to a lung complication.